Comprehensive genomic profiling reveals a unique genomic landscape in solid tumors in an Indian cancer cohort of 1000 patients: a single institutional experience - Mithua Ghosh; Sheela Mysore Lingaraju; Krishna C.R; Gautam Balaram; Ramya Kodandapani; Vijay E; Vijay K; Suhas N; Devika H; Shekar Patil; Satheesh Chiradoni Thungappa; Somorat Bhattacharjee; et al. (Scientific Reports)
Abstract The use of Comprehensive Genomic Profiling (CGP) in clinical practice to detect broad-spectrum therapeutic, prognostic, and predictive biomarkers, including tumor mutational burden (TMB), microsatellite instability (MSI), somatic BRCA (sBRCA) and other homologous recombination repair genes (HRRs) provides a more cost-efficient and tissue-preserving approach than serial single-biomarker analysis. A total of 1000 biopsy-proven cancer patients at the HCG cancer center were profiled in an IRB-approved prospective study. The findings were discussed in the multidisciplinary molecular tumor board (MTB), and recommendations were documented in electronic medical records (EMRs) for clinical management and follow-up. A total of 1747 genomic alterations were detected (mean 1.7 mutations/sample), with 80% of patients having genetic alterations with therapeutic and prognostic implications (Tier I-32%, Tier II-50%). CGP revealed a greater number of druggable genes (47%) than did small panels (14%). Tumor-agnostic markers for immunotherapy (IO) were observed in 16% of the current cohort, based on which IO was initiated. In 13.5% of the cohort, alterations in the HRR pathway including sBRCA (5.5%) were detected providing an option for treatment with platinum or PARP inhibitors. Other significant alterations included those in EGFR, KRAS/BRAF, PIK3CA, cKIT, PDGFRA, ARID1A, ARID2, and FGFR. RNA sequencing revealed 55 + RNA alterations, including those in TMPRSS-ERG, RPS6KB1-VMP1, EML4-ALK, NTRK, PDGFRA and EWSR. Clinical outcome data were available via EMR for 618 patients (62%), out of whom 419 patients had druggable mutations (67%; 95% CI 88.9–93.9%) and 39 patients had 1 or more mutations with prognostic implications. However, only 200 patients (44%; 95% CI 39.1–48.1%) were included in the MTB discussion. Based on genomics reports, the treatment regimen was changed for 137 and 61 patients with and without clinical inputs from the MTB, respectively. The overall change in therapy based on CGP in the clinical cohort was 43%, which was greater in patients enrolled for MTB than in patients who had not undergone MTB. At the interim analysis, with a median follow-up of 18 months (range 12–24 months) after the change in therapy as per genomics report, 97 patients (71%) were found to be alive thus establishing the importance of CGP and MTB in personalized genomics-driven treatment.